Empowering Children Through a Mobile Application for Sexual Abuse Prevention: The Supporting Roles of Parents and Teachers in a Cluster-Randomized Controlled Trial in Indonesia - Tetti, Solehati; Yanti, Hermayanti; Helmy, Hazmi; Mira, Trisyani; Muhammad, Yusuf; Cecep Eli, Kosasih; Rachelya Nurfirdausi, Islamah (Dove Medical Press Limited, 2025)
Background: Child sexual abuse (CSA) is a significant issue, partly due to the lack of evidence-based prevention programs involving parents and teachers. In Indonesia, no integrated CSA prevention app exists for parents, teachers, and children. This study evaluated the effectiveness of the Child Sexual Abuse Prevention Mobile Application (CSAP_Mob App) in empowering parents and teachers to improve children’s knowledge and attitudes, as well as parental and teacher knowledge and communication practices. The primary outcome is the change in children’s knowledge and attitudes, while the secondary outcome is the change in knowledge and communication practices among parents and teachers. Methods: This cluster-randomized controlled trial included 56 teachers, 207 parents, and 212 children from elementary schools in two regencies in West Java, Indonesia. The intervention group received sexual abuse prevention education for four weeks via the CSAP_Mob App, while the control group followed standard school procedures. Effectiveness was assessed through pre- and post-tests measuring parents’ and teachers’ knowledge and communication practices, as well as children’s knowledge and attitudes toward recognizing and avoiding CSA. We used the Wilcoxon test to examine changes within groups and the Mann–Whitney U-test to compare differences between groups and calculate effect sizes. Results: The intervention group showed a significant improvementin knowledge and communication practices among parents (p=0.001; 0.015) and teachers (p=0.001; 0.001), Conversely, parents (p=0.214; 0.870) and teachers (p=0.025; 0.936) in the control group showed no significant improvement. Both groups of children improved in knowledge and attitudes (p = 0.001). Significant differences were observed between the control and intervention groups following the intervention in children’s knowledge (p=0.001) and attitudes (p=0.001), as well as in parents’ knowledge (p=0.001), and teachers’ knowledge (p=0.001) and communication practices (p=0.001). Moderate effect size gains in children’s knowledge and attitudes, as well as in parents’ and teachers’ knowledge and communication practices, indicate the app’s effectiveness with parent and teacher involvement. Conclusion: CSAP Mob Application effectively improved children’s knowledge and attitudes on sexual abuse prevention, as well as parents’ and teachers’ knowledge and communication practices. These findings highlight the importance of empowering parents and teachers through mobile-based interventions to strengthen child sexual abuse prevention efforts.